SOIL PHYSICAL PROPERTIES IN A LONG-TERM CONSERVATION SYSTEM FOR ONION - Muetanene, Belo Afonso; Mafra, Ãlvaro Luiz; Albuquerque, Jackson Adriano; Peternelli, Luiz Alexandre; Kurtz, Claudinei (REVISTA DE AGRICULTURA, 2021)
The objective of this study was to evaluate soil physical properties under different cropping systems for onion. The study was conducted on an Inceptisol in Ituporanga, Santa Catarina state, Brazil. We evaluated eight cropping systems for onion: T1: maize-onion succession; T2: common vetch-maize/rye+fodder radish-onion-maize/rye+fodder radish-common bean; T3: rye-onion-maize/black oat-maize; T4: onion-velvet bean succession; T5: rye-onion-millet/black oat-onion-millet; T6: rye-onion-velvet bean succession; T7: onion-velvet bean+millet+sunflower succession. Treatments from T1 to T7 were conducted under no-tillage system (NTS) and T8: maize-onion succession under a conventional tillage system. We used the randomized complete block design, with five replications. Undisturbed soil samples were collected at the 0-5, 5-10 and 10-15 cm soil layers and we evaluated the following soil physical properties: geometric mean diameter of aggregates, total porosity, macroporosity, microporosity, bulk density and the ratio macroporosity/ total porosity. The data analysis was performed using univariate statistics, principal components analysis (PCA) and cluster analysis (CA). Based on the cropping systems characteristics, the CA divided them into three groups: group 1: T7; group 2: T1, T2, T3, T4, T5, T6; and group 3: T8. T8 showed evidence of soil physical quality deterioration at the soil surface, T7 presented the best soil physical properties.